Web-Based Geographic Information System Application For The Location Of The Tire Patching Workshop In South Padang District - Ramadhan, Okki; kamal, Ahmad; Sularno, Sularno (Jurnal Sistem Informasi Dan Informatika, 2025)
This study aims to design and build a GIS-based Tire Repair Workshop Information System Application that can be used for data collection of tire repair workshop locations in Padang Selatan District, a container to make it easier for users to find tire repair workshop locations around Padang Selatan District if a tire leak occurs on a vehicle and can help the economic cycle for tire repair workshop business owners, especially around Padang Selatan District. In making the software in this study, the author uses the PHP programming language and MySQL as a database. The final result of this study is a GIS-based application program that is expected to help users obtain information related to the Tire Repair Workshop in Padang Selatan District.